Dingsanak Peduli TB: Caregiver Empowerment to Improve Knowledge and Skills in Families of TB Patients - Yulia Yunara; Herawati; Lola Illona Elfani Kausar; Alfian Nur; Yaumil Hafsani Siregar (LKP KARYA PRIMA KURSUS, 2025)
Tuberculosis (TB) remains a pressing health concern in Indonesia, with caregivers playing a decisive role in supporting treatment adherence and preventing household transmission. This community engagement project, conducted in Desa Keliling Benteng Ulu, South Kalimantan, sought to empower caregivers through structured educational and skill training using the Dingsanak Peduli TB module. Fifteen caregivers of TB patients participated in interactive sessions that combined knowledge transfer, demonstration, and skills practice. Knowledge assessment was performed before and after the intervention using domain-specific questionnaires covering TB transmission, household prevention, treatment adherence, family roles, and recovery support. Results showed a significant increase in mean knowledge scores from 56,7 to 85,3. The most pronounced improvements were observed in household prevention practices and treatment adherence, with caregivers reporting greater self-confidence in their caregiving roles. These findings highlight that structured caregiver empowerment can enhance household capacity in TB care and represent a scalable, community-based strategy to strengthen Indonesia’s TB control efforts.